A Feasibility Study Of 100 Kl/Day Bioethanol Plant From Sugarcane Production As Part Of National Energy Mix Strategy - Oetomo, Dedy Setyo (Sainteks: Jurnal Sain dan Teknik, 2025)
This study evaluates the technical and economic feasibility of constructing a 100 KL/day bioethanol production plant from sugarcane as part of Indonesia's national energy mix strategy. The research employs comprehensive analysis including mass balance, energy balance, technical design, and financial evaluation. The plant design utilizes fermentation and distillation processes with an annual production capacity of 36,500 KL bioethanol. Mass balance calculations show that 1,200 tons/day of sugarcane feedstock is required, producing 100 KL ethanol, 480 tons bagasse, and 120 tons vinasse daily. Energy balance analysis indicates the plant can achieve energy self-sufficiency through bagasse combustion for steam and electricity generation. Technical evaluation confirms the feasibility of implementing proven bioethanol production technology. Financial analysis reveals total investment requirement of USD 45.2 million with Net Present Value of USD 12.8 million, Internal Rate of Return of 18.5%, and payback period of 6.2 years at 12% discount rate. Sensitivity analysis demonstrates project robustness against feedstock price and ethanol selling price variations. The study concludes that the bioethanol plant is technically feasible and economically viable, contributing significantly to Indonesia's renewable energy targets and rural economic development while reducing dependency on fossil fuel imports